Non-medical Prescribing in the United Kingdom - Franklin, Penelope Mary (Springer International Publishing : Imprint: Springer, 2017)
This book explores key developments in Non-medical Prescribing in the UK. Addressing the needs of countries in the European Market and beyond, which have been closely watching UK developments and would be interested in embedding or developing counterparts of their own. Featuring chapters by clinicians, leaders and practitioners in the UK Non-medical Prescribing arena, it identifies both current and potential future developments. Attention is paid to the different prescribing practices and governance within the four countries constituting the United Kingdom. Many lessons have been learned along the way and the purpose of this book is to share these lessons, tog ether with best practice examples in connection with the implementation of nurse/health professional led patient care, implementation of patient centered practice, and governance. Designated Registered Practitioners who have completed an enhanced training now receive a professional body qualification which enables them to prescribe within their scope of practice as Non-medical Independent Prescribers and, providing that they are competent, from anywhere within the British National Formulary independently of doctors; for Nurses, this also includes most controlled drugs. The book will be of interest to policy makers and to forward-looking professionals and practitioners in the diverse European Health and Social Care market.
Keywords: Medicine.; General practice (Medicine).; Nursing.; Primary care (Medicine).; Pharmacotherapy.; elektronické knihy; electronic books